Pedagogy of Hope for Global Social Justice Sustainable Futures for People and the Planet - Bourn, Douglas; Tarozzi, Massimiliano (Advances in Education for Sustainable Development and Global Citizenship, 2023)
Following Paulo Freire and his concept of pedagogy of hope, this open access book explores the educational role of hope as an approach to learning about global issues in different areas of the world. Climate change, racism, and the COVID-19 pandemic have shown more than ever the need for a global shift in education policy and practice. This book provides a conceptual framework of global education and learning and the role it can play in addressing these social and environmental challenges. Written by scholars based in Australia, Brazil, Canada, China, Ghana, India, Italy, Portugal South Africa, Spain, the UK and the USA, the book addresses a range of local and global issues from global citizenship education in Latin America to training teachers in global education. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Knowledge Unlatched.